METODE KUIS DALAM MENINGKATKAN KUALITAS PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM PADA SISWA KELAS IV MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Nisa Jamilah, Shofi; Iswandi, Irvan; Humaeroh, Iis (Sindoro: Cendikia Pendidikan, 2024)
Education is a conscious and planned effort to achieve predetermined goals, including in the context of teaching Islamic Cultural History (Sejarah Kebudayaan Islam - SKI). In the teaching process, teachers need to implement various effective strategies to ensure that learning objectives are achieved successfully. The approaches used by educators should facilitate students in understanding the material in an easy, effective, and clear manner. Thus, the material delivered becomes not only information but also something that students can utilize in their daily lives. This study aims to analyze the implementation of the quiz method in improving the quality of learning and how the quiz method can optimize the quality of teaching Islamic Cultural History (SKI) for fourth-grade students at Madrasah Ibtidaiyah Ma’had Al-Zaytun. The study employs a qualitative approach, emphasizing an in-depth understanding of the application of the quiz method in the context of teaching SKI to fourth-grade students at the Madrasah. The sample selection was conducted using random sampling techniques, and data were collected through interviews with teachers and students, direct observations during the learning process, and relevant school documentation. The findings of the study indicate that the implementation of the quiz method significantly improves the quality of learning. This is evident from the increased interest, motivation, and engagement of students in learning activities. Students no longer remain passive listeners but actively participate in the learning process through discussions, question-and-answer sessions, and collaborations.Additionally, the quiz method enhances students' collaboration and teamwork skills, as well as significantly improves their understanding and retention of the material taught by the teacher. Through the implementation of this quiz method, the learning process becomes more interactive and enjoyable, thereby achieving educational goals more optimally. Key Words: quiz method, Islamic Cultural History, learning quality, Madrasah Ibtidaiyah.